(untitled) (Ameghiniana, 2014)
"Meniscate striated traces are recorded from Perrnian fluvial deposits of the La Colina Formation (Paganzo Group) at Los Colorados de Patquía (La Rioja Province). These structures are characterized by their remarkable well developed striations, oblique to the margins of unbranched and unwalled traces. Taxonornic assessment of these structures must await clarification of the actual nature of the ichnogenus Scoyenia and its relationship with Taenidium. They are interpreted as arthropod feeding structures (fodinichnia), Meniscate striated traces characterize firrn substrates and crosscut a softground ichnofauna ascribed to the Scoyenia ichnofacies. Trace makers probably colonized the desiccated rnargins of a floodplain water body. A review of the ichnologic record of nonmarine firmgrounds shows the widespread establishment of trace fossils in cohesive sedirnents during the Mesozoic and only an incipient development during the Palaeozoic, The Palaeozoic examples undoubtely ascribed to invertebrates are known from the Perrnian and seem to record."